1974
DOI: 10.1063/1.1655065
|View full text |Cite
|
Sign up to set email alerts
|

Switching in organic polymer films

Abstract: Memory and threshold switching processes are described, as observed in systems consisting of thin (∼0.5 μ) polymer films (polymethylmethacrylate, polystyrene, polyethylmethacrylate, polybutylmethacrylate) between inert electrodes (graphite, molybdenum, NESA glass). The memory off-state is highly linear, in contrast to the corresponding characteristics of multicomponent chalcogenide glasses. Switching speeds are probably similar or, at any rate, ≪10−7 sec.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…Figure 7͑b͒ shows the equivalent circuit model of an N-layer memcapacitor. Another interesting model extension can be achieved if a memristive material is used ͑e.g., VO 2 films 5 or an organic memristive material [25][26][27][28] ͒ instead of the usual dielectric between the internal layers. Then, in the equivalent circuit model, the role of nonlinear resistors will be played by memristors.…”
Section: Equivalent Circuit Modelmentioning
confidence: 99%
“…Figure 7͑b͒ shows the equivalent circuit model of an N-layer memcapacitor. Another interesting model extension can be achieved if a memristive material is used ͑e.g., VO 2 films 5 or an organic memristive material [25][26][27][28] ͒ instead of the usual dielectric between the internal layers. Then, in the equivalent circuit model, the role of nonlinear resistors will be played by memristors.…”
Section: Equivalent Circuit Modelmentioning
confidence: 99%
“…In this case the memory effect is attributed to electric field-induced charge transfer between the metal nanoparticles and the small organic molecules. Segui et al (1976) and Henish & Smith (1974) suggested that the switching mechanism (i.e. between the two conductivity states) in their devices is due to the formation of conductive filaments between the top and bottom metal electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The PVCz doped with 12 was used as a switching sample. TheN, value for the doped PVCz calculated from the observed V,h using equation V,h = ed 2 …”
Section: Resultsmentioning
confidence: 99%